The Concept of Halal as the Foundation for the Development of the Halal Industry in Islamic Economic Law - Fakhry Fadhil; Muflih Adi Laksono; Nurrohman Nurrohman (STAI Al-Mas'udiyah, 2026)
The concept of halal was initially understood as a religious provision related to what is permissible for Muslims to consume. However, over time, the meaning of halal has expanded significantly and is no longer limited to the aspect of consumption alone. Halal has developed into a broader value system that encompasses various economic activities, including production, distribution, and consumption of goods and services. This development has led to the emergence of the halal industry, which integrates Islamic principles into various sectors such as food, pharmaceuticals, cosmetics, fashion, finance, and tourism. This study aims to analyze the concept of halal as a foundation for the development of the halal industry from the perspective of Islamic economic law. The research employs a normative approach using a literature study method by examining Islamic legal sources, including the Qur’an, hadith, fiqh literature, and regulations related to halal product assurance. The findings indicate that the concept of halal is not only related to the legal permissibility of products but also reflects values of justice, transparency, cleanliness, and public welfare in economic activities. In Indonesia, the development of the halal industry is supported by regulations through Law No. 33 of 2014 on Halal Product Assurance, implemented by Halal Product Assurance Organizing Agency with the involvement of Indonesian Ulema Council in determining halal fatwas.